AN APPLICATION OF COOLING SYSTEM TEMPERATURE AS PERFORMANCE IMPROVEMENT SOLAR PANEL - Nur Aisyah Siregar; Siti Anisah; Solly Aryza (INFOKUM, 2022)
Solar panels or solar cells are one of the renewable energy sources. Solar cells can convert sunlight into dc electrical energy. However, the main problem with solar cells is that the energy produced is not stable. The surface of the Solar cell board has a maximum temperature which affects the output of the solar cell. From this research, the writer will make the surface cooling of the solar cell board using a heatsink fan. The maximum surface temperature of the solar cell board reaches an average of 45 oC. If the temperature exceeds 45 oC it will reduce the output of the solar cell. In this study, the average temperature on the surface of the solar cell board, from 9 am to 3 pm was around 50.14oC and the average output of the solar cell reached 18.80 Volts. Meanwhile, the average temperature of the solar cell with the use of heatsink cooling is 36oC. The average output of the panel is 19.11 volts. Thus, by using a solar cell surface board cooling system using a heatsink, it has an average temperature decrease of 28.20% and an increase in output (Output) can be increased by 1.64% from the efficiency of the Solar cell which is only 12.1%.